Breastfeeding and infant growth in offspring of mothers with hyperglycaemia in pregnancy: The pregnancy and neonatal diabetes outcomes in remote Australia study. Issue 6 (20th February 2022) - Longmore, Danielle K.; Titmuss, Angela; Barr, Elizabeth; Barzi, Federica; Simmonds, Alison; Lee, I‐Lynn; Hawthorne, Eyvette; Derkenne, Ruth; Connors, Christine; Boyle, Jacqueline; Zimmet, Paul; O'Dea, Kerin; et al.
Summary: Background: Benefits of breastfeeding on infant growth in children born to mothers with gestational diabetes mellitus (GDM) are uncertain. Objectives: To describe growth trajectories between birth and 14 months according to breastfeeding and maternal hyperglycaemia in pregnancy, and assess associations between breastfeeding and 14 month growth outcomes among children born to mothers with GDM. Subjects/methods: Data on 258 Aboriginal and Torres Strait Islander infants from the PANDORA study born to mothers with normoglycaemia ( n = 73), GDM ( n = 122), or with pre‐existing type 2 diabetes ( n = 63) in pregnancy were assessed. Infant weight and BMI growth trajectories according to predominant breastfeeding at 6 months and hyperglycaemia in pregnancy were developed using mixed‐effect models and cubic splines. Associations between breastfeeding and 14‐month growth outcomes ( z ‐scores: weight‐for‐age, weight‐for‐length and BMI) were evaluated using linear regression in a subgroup of infants born to mothers with GDM. Results: Predominantly breastfed infants had lower BMI trajectories compared to those not predominantly breastfed, irrespective of maternal hyperglycaemia in pregnancy status ( p < 0.01 for all groups), and lower weight trajectories among those born to mothers with GDM ( p = 0.006). Among offspring of women with GDM, predominant breastfeeding was only associated with lower weight‐for‐age at 14 months, however adjusting for maternal obesity, smoking, and parity attenuated observed associations. Maternal obesity remained significantly associated with greater infant growth. Conclusions: Predominant breastfeeding was associated with reduced growth among children born to women with and without hyperglycaemia in pregnancy. However, among children exposed to GDM in utero, maternal obesity largely explained this association.